Pengaruh Budaya Kerja, Motivasi Kerja Dan Kepemimpinan Terhadap Kepuasan Kerja Pegawai - Maria; Ahmad Anshari; Rusaini Hasibuan; Ahmad Tarmizi Nasution; Apriati Bulolo; Nur M. Ridha Tarigan; M. Nelson Pinem (ARBITRASE: Journal of Economics and Accounting, 2023)
The formulation of the problem in this study is how the influence of work culture on job satisfaction. How does the influence of work motivation on job satisfaction. How does the influence of leadership on job satisfaction. How does the influence of work culture, work motivation and leadership on job satisfaction. The purpose of this study was to determine and analyze the effect of work culture on job satisfaction. To know and analyze the effect of work motivation on job satisfaction. To find out and analyze the influence of leadership on job satisfaction. To know and analyze the effect of work culture, work motivation and leadership on job satisfaction. The sample in this study amounted to 82 employees. The data analysis technique used in this study is multiple linear regression analysis. The results of this study explain that work culture has a positive and significant effect on job satisfaction. Work motivation has a positive and significant effect on job satisfaction. Leadership has a positive and significant effect on job satisfaction. Work culture, work motivation and leadership have a positive and significant effect on job satisfaction.